Adolescent Exposure to Methylphenidate Increases Impulsive Choice Later in Life - Abbas, Zarish; Sweet, Arwen; Hernandez, Giovanni; Arvanitogiannis, Andreas (Frontiers in Behavioral Neuroscience, 2017)
Background: The psychostimulant methylphenidate (MPH) is known to temporarily reduce impulsive choice and promote self-control. What is not sufficiently understood is how repeated treatment with MPH affects impulsive choice in the long run, and whether any such effect is contingent on exposure at certain developmental stages. Methods: Using an animal model for impulsive choice, we examined first whether giving MPH through early adolescence alters delay discounting, an operational measure of impulsive choice, later in adulthood. We then tested whether equivalent long-term effects are observed if exposure to the drug occurred during adulthood. Starting on postnatal day 25 or postnatal day 60, male rats received one of a range of doses of MPH for 10 consecutive days. Twenty-six days later, all rats were trained to choose between a lever that produced a small immediate reward and a lever that produced a large reward after a range of delays. Results: Rats showed a long-term decrease in the selection of the delayed larger reward when treated with moderate doses of MPH during early adolescence, but not when treated with the lower or higher doses. In contrast, no differences were observed in the selection of the delayed larger reward in animals that were treated with various doses of MPH during adulthood. Conclusions: Our findings suggest effects of MPH on impulsive choice that are contingent on dosage and on the developmental period of exposure. When administered during adolescence, moderate doses of MPH increase impulsive choice long after the end of treatment, whereas these same doses administered during adulthood were without effect